Incidence of Helicobacter hepaticus and its relation to gallbladder carcinoma (Journal of Pathology of Nepal, 2011)
Background: Chronic cholecystitis due to cholelithiasis is one of the most common hepatobiliary surgical disorders. Bacteria are found in high concentration in bile and stone. Helicobacter hepaticus is a gram negative, micro-aerobic bacterium, curved to spiral in shape which shows positivity with urease, catalase and oxidase. Bacterial infection may be one of the causes for the pathogenesis of gallstone formation as most gallstones are colonized by a bacterial biofilm. Materials and Methods: This was a retrospective study done in the Department of Pathology, Kathmandu Medical College for a one year period, between June 2007 and July 2008. A total of 277 cases were included in the study. Results: Amongst the 277 cases, 270 cases (97.4%) were diagnosed as chronic cholecystitis and 7 cases (2.5%) were diagnosed as gallbladder carcinoma. All the cases diagnosed as gallbladder carcinoma was of adenocarcinoma except a single case of adenosquamous carcinoma. Fifty three out of the 277 cases (19.13%) showed positivity in Warthin Starry Silver stain. Out of the 7 cases diagnosed as gallbladder carcinoma, 5 cases were found to be positive Warthin Starry Silver stain. Conclusion: The role of Helicobacter hepaticus infection as a nidus for formation of gallstone that ultimately leads to malignancy is controversial and its dominant role in the pathogenesis of carcinoma is yet to be determined. Keywords: Gallbladder carcinoma; Helicobacter hepaticus; Warthin Starry Silver stain. DOI: http://dx.doi.org/10.3126/jpn.v1i2.5406 JPN 2011; 1(2): 122-125